HUBUNGAN POWER OTOT TUNGKAI DAN KELENTUKAN PERGELANGAN TANGAN DENGAN KETEPATAN JUMP SMASH BULU TANGKIS PADA CLUB PB. IDILA SIBERAKUN - Rexi Hadi Eka Putra; Slamet Slamet; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The Problem in This Study is whether there is a Relationship between leg Muscle Power and Wrist Flexibility with the Accuracy of Badminton Jump Smash on the Pb Idila Siberakun. The Purpose of This Study was to determine the significance of the Relationship between leg Muscle Power and Wrist Flexibility with the accuracy of Badminton Smash Jump at Club in the PB Idila Siberakun The Type of Research is Correlational. The Population used was PB Idila Siberakun athlete who numbered10 people. In the study of the relationship of Leg Muscle Power variable (X1) to the accuracy of Smash Badminton (Y), there is a positive and meaningful relationship with correlation coefficient of r = 0.818, the significance is 4.022 means tcount (4.022)> t table (2,306), so H1 is accepted. for the variable relationship of Wrist Determination (X2) to the Smash Accuracy of Badminton (Y), there is a positive and meaningful relationship with correlation coefficient of r = 0.823, the meaning is 4.104, means tcount (4.104)> t table (2.306), so H2 is accepted. and the relationship of variables of Leg Muscle Power and Joint Detection of Smash Badminton Accuracy with a correlation coefficient of R = 0.831 where the significance was tested by F-test and obtained fcount of 7.82, meaning tcount (7.82)> t table (4.74) and H3 is accepted. Based on the results of research and data processing using statistical research procedures, it was concluded that Leg Muscle Power and Explosive Power Variables had a significant relationship to Smash Badminton Accuracy and could be applied to the ClubPB. Idila SiberakunKey Words: Leg Muscles Power , Flexibility of Wrist, Jump Smash